Sustainable desalination technologies: Avenues for cooperation in the Indo-Pacific. (2nd January 2019) - Kishor, Maitreyee Shilpa; Agarwala, Nitin
ABSTRACT: Desalination technologies using ocean thermal energy are a sustainable method of producing fresh water, especially for ecologically fragile regions and small island nations. India has tested this technology in the Lakshadweep Islands and has the capability to share it with its Indo-Pacific partners. This paper explores the benefits, market and prospects of sustainable desalination technologies in the Indo-Pacific region. It outlines the possible multilateral platforms that can be used to share this technology and the various challenges that this endeavour faces. The paper concludes that such technology sharing will have a positive impact on regional integration and will strengthen India's position as a responsible regional power promoting the blue economy.